Graphical web based tool for generating query from star schema - Anbar, Mohammed; Ku-Mahamud, Ku Ruhana (2009)
This paper presents the development of a graphical SQL query tool that allows novice and non-technical users to navigate through database tables and generate their own queries.The tool enables the query output to be presented in graphical and tabular forms, which can help users, especially top management in better understanding and interpreting query results.The algorithms to construct complex SQL query from star schema in databases is also presented.